(untitled) (Journal of Economic Research & Business Administration, 2016)
In this article the problems of insufficient science in the educational system and, as a result, the formation of not competitive human capital were studied. The parameters that determine the increasing of human capitalcompetitiveness and innovative development of the region, as well as the main indicators that show expenditures on science, quantity of higher educational institutions and quantity of students, and quantity of scientific organizations were analyzed. Based on the conducted analysis, the author proposed a win-win mechanism of interactions between participants of innovative system, which on the level of higher educational institutions will contribute to formation of competitive human capital in the country and consequently will contribute to innovative development of the national economy.